Reassessing methods to close the nuclear fuel cycle. (November 2020) - Dixon, B.; Hoffman, E.; Feng, B.; Davidson, E.; Hays, R.; Worrall, A.; Hansen, J.; Fei, T.; Hiruta, H.; Peterson-Droogh, J.; Ganda, F.; Betzler, B.; et al.
Highlights: Transitioning US nuclear fleet to a closed fuel cycle can be achieved during the period when the current reactors need replacement. This closed fuel cycle would require 1% as much front-end resources and yield 5% as much waste compared to the existing cycle. Such a transition would require a significant inventory of fissile material such as U/Pu from recycled used fuel or HALEU. The use of HALEU may be more favorable because it is less constrained and may be more economical. Abstract: This paper presents the major takeaways from studies conducted over several years that were focused on transitioning the U.S. nuclear infrastructure from the current once-through fuel cycle to one in which fuel is continuously recycled in fast reactors. These studies involved simulating and analyzing numerous example scenarios of fuel cycle transition with various assumptions on technology, policy, and material utilization strategies. Among the many findings, perhaps the most important is that under certain conditions, the use of high-assay low-enriched uranium to start up a fleet of fast reactors may be more favorable compared to using recycled Pu from thermal reactors since it is less constrained by other technologies and may even be more economical.